The study of cadastre issues involving the first grade land status in Seberang Perai Utara, Penang / Muhammad Dzul Ahwal Muharram Mohd Zuki - Mohd Zuki, Muhammad Dzul Ahwal Muharram (2018)
In Malaysia, the land matters is vested to the State Authority. The State Authority has a full power in disposing of land either to individuals or organizations qualified under the law. This paper is about the study of cadastre issues involving the first grade land status in Seberang Perai Utara,Penang. The study area is covered Seberang Perai Utara,Penang in term of the First Grade Land. The data collected from the State District Land Office(PTD), Department of Land and Mines (PTG) and Department of Surveying and Mapping Malaysia(DSMM) to complete the research. The aim of this research is to analyse and produce a graphic repesentation of the first grade land status in Seberang Perai Utara,Penang for distinguish first grade land status between the others land status. The objectives for this research is to investigate the first grade land status and characteristic,to analyse the first grade land based on allocated perspective and to produce the model of first grade land using MapInfo software.These methodology involving about discussion,data acquisition and analyse of first grade land status.These methodology is to produce the modelling for first grade land status and to analyse in term of tax,status,temporal,exception form and condition of first grade land.Finally,this analyse is to produce the modelling where consist of the characteristic of first grade land to support the it’s implementation.As the conclusion,this first grade land model will be beneficial for State Authority for future development in Malaysia.